Measuring Sociolla Services Quality Influence To Customer Satisfaction and Behavioral Intention (The Indonesian Journal of Business Administration, 2021)
In the midst of many online shopping transactions through e-commerce in Indonesia, Sociolla offers an e-commerce that specifically sells beauty products such as make-up, skincare, and beauty tools. Along with this phenomenon, problems about quality of services on e-commerce have started to raised. This study will analyze the effect of e-service quality and perceived product quality on customer satisfaction and behavioral intention in the case of e-commerce. The method used is a quantitative method by distributing questionnaires to 302 consumers who experienced in buying toner products from Sociolla. The data were analyzed by doing factor analysis and path analysis using SPSS and SmartPLS. The results show that the each perceived product quality and e-service quality have a positive and significant influence on customer satisfaction. In addition, the customer satisfaction resulting from the quality provided by e-commerce has a positive and significant influence on behavioral intention. Last, e-service quality provided by e-commerce also has a positive and significant influence on behavioral intention. Keywords: e-service quality, perceived product quality, customer satisfaction, behavioral intention, e-commerce.